Implementation of Tri Bakti PMR and Seven Basic Principles in Daily Life - Rahmadani, Aulia; Rika, Amelia; Salsabila, Isal; Usiono, Usiono (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2023)
The aim of this research is to determine the implementation of the Tri Bakti PMR and the seven basic principles in everyday life. The method used by researchers is a qualitative research method with a population of participants and Jumbara coaches. Meanwhile, the research sample was 7 people consisting of 6 jumbara participants and 1 supervisor. The data collection technique carried out by researchers in this study used observation and documentation interview techniques. Based on the results of the research, it shows that implementing the Tri Bakti PMR and the seven basic principles in everyday life is very important, starting from maintaining personal hygiene, carrying out mutual cooperation activities. working together in the community and strengthening and increasing friendship relations. Applying the basic principles can be done by helping someone without discrimination, voluntarily, fairly and also by being independent, such as caring for one's own wounds. It can be concluded that the application of the Tri Bakti and basic principles will train people to be good at helping others without discrimination, without expecting rewards and without discrimination and can also train a sense of sympathy for helping people and a sincere attitude as well as inner satisfaction for having helped people.